PENINGKATAN SKILL PERPAJAKAN UMKM YAYASAN KAWIS - Auliffi Ermian Challen; Imelda Sari; Muhammad Faisal; Elmanizar Elmanizar; Subhan Harie (LPPM Universitas Bina Bangsa, 2024)
The level of compliance in making tax payments is still low in Indonesia. However, the tax potential that can be generated by MSMEs needs to be a concern. Because the tax contribution of MSMEs is still low. Many MSME actors do not yet have an understanding and knowledge of tax obligations. This community service activity aims to socialize and provide tax training regarding MSME tax obligations and the practice of filling out MSME individual tax returns. Based on the objectives that have been set, training is carried out in February and March online. The training participants were MSMEs under the guidance of the Kawis Foundation. The results of the training have been able to provide knowledge about tax obligations and how to fill out and report tax returns. In addition, this training also encourages participants to obey and comply with applicable tax provisions in Indonesia